High average power nanosecond pulsed single longitudinal mode diamond Raman laser in the 1.6 µm waveband - Weifeng Tan; Yisen Wang; Peining Chen; Rongzhuo Chen; Siqi Zhu; Hao Yin; Zhen Li; Zhenqiang Chen; Shibo Dai (Functional Diamond)
Realizing high average power nanosecond pulsed single longitudinal mode laser sources around 1.6 μm are of intense interest for applications as diverse as range finding, remote sensing, and environmental monitoring. Herein, we first demonstrate a high average power and high beam quality nanosecond pulsed eye-safe diamond Raman laser at 1634 nm, which is intracavity driven by an acousto-optic Q-switched two-crystal Nd:YVO4 laser at 1342 nm. By exploiting the subtly designed dynamically stable resonator and the thoroughly optimized acousto-optic modulator, excellent beam quality and substantial power improvement have been confirmed. Under the incident pump power of 60.9 W, the highest multimode average output power of 6.92 W has been achieved with the repetition rate of 25 kHz and the duty cycle of 8%, corresponding to the pulse duration of 8.8 ns and the peak power of 31.5 kW. Subsequently, by inserting a fused silica etalon in the high-Q fundamental cavity, the average output power for single longitudinal mode operation has been creeping up to 2.56 W with the aid of the high precision temperature controlling and the enlarged beam diameter on diamond, where the pulse duration and the spectral linewidth are 8 ns and 180 MHz, respectively. The beam quality is maintained with M2 < 1.3 across the entire output power range.